Mimikri, Mockery, dan Resistansi Gaya Hidup Pribumi terhadap Budaya Kolonial Belanda dalam Tetralogi Pulau Buru - Hardiningtyas, Puji Retno (METASASTRA: Jurnal Penelitian Sastra, 2018)
This research discusses mimicry, mockery, and resistance of indigenous and colonial lifestyle as a result of Indies cultural contact in the tetralogy of Pramoedya Ananta Toer’s “Pulau Buru”. The purpose of this research is to describe  the reality of indigenous lifestyle in the Buru tetralogy especially at mimicry, mockery, as well as resistance from colonized people. Data collection method of this research is the literary study of reading-record technique. The data are analyzed by  applying the analytical descriptive method with understanding and interpretation technique. Homi K. Bhabha's postcolonial theory is used to examine mimicry, mockery, and resistance problems. The result of the research shows that cultural contact between colonialists and colonized people in the Indies has engendered Indies culture. The existence of the mixing of Indies culture influenced the occurrence of mimicry to western culture performed by indigenous leaders. In contrast, the emergence of mockery against the indigenous was done by Dutch colonial leaders who did not like the indigenous alignment/establishment. However, behind the events of mimicry and mockery, the presence of Minke and Nyai Ontosoroh is as the strong figures.  It is intended for indigenous cultural resistance  as a form of resistance to colonial occupation in the Dutch East Indies.